Reconstruction Concept of Deliberation to Build Religious Moderation among Muslims - Rhain, Ainur (Universitas Muhammadiyah Surakarta, 2023)
The Qur'an came with the concept of moderation in the form of deliberation. The concept of moderation needs to be taught because today's society quickly blames, degrades, acts harshly, and even kills different groups. The purpose of this study is to build religious moderation among Muslims. The research used to parse the problem is library research, focusing on verse 159 of Surat Ali Imran as the construction of the concept of deliberation. This letter carries the message of religious moderation among Muslims with gentle teachings, open-minded, not degrading groups, madhab, or other Islamic organizations. (Faddun). It is not easy to solidify. (gholid al-qolbi), respecting the opinions of others (Fa'fu anhum), Deliberation to create moderation, and Accepting Dissent wisely (al-azmu). Deliberation must be formed into concepts and formulations to build moderation among Muslims. Researc's contribution is to build a more open mindset of Muslims, respect differences of opinion, not easily blame and anarchists’ different groups.